2017
DOI: 10.21580/ns.2017.1.1.1992
|View full text |Cite
|
Sign up to set email alerts
|

PENGARUH PENAMBAHAN LABU KUNING (Cucurbita moschata) dan Ikan Gabus (Ophiocephalus striatus) TERHADAP MUTU ORAGNOLEPTIK, KADAR PROTEIN DAN VITAMIN A BISKUIT

Abstract: <p><em>Nutrition potential and availability of pumpkin and cork in Indonesia are abundant, so diversification of pumpkin and cork fish in biscuit making is expected to be a more nutritious food alternative. This study was an experimental study using a complete randomized design consisting of three treatments, one control and two replications. This study was conducted in January - June 2016. Observations were made on organoleptic characteristics and protein content of biscuits. The subjectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
2
0
3
Order By: Relevance
“…The Maillard reaction causes a loss of amino acids. The Maillard reaction does not require high temperatures, but the reaction rate will increase sharply with increasing temperature and drying time[30].In this study, protein content increased along with the addition of snakehead fish[31]. reported that the concentration addition of snakehead fish increased the protein content of biscuits.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…The Maillard reaction causes a loss of amino acids. The Maillard reaction does not require high temperatures, but the reaction rate will increase sharply with increasing temperature and drying time[30].In this study, protein content increased along with the addition of snakehead fish[31]. reported that the concentration addition of snakehead fish increased the protein content of biscuits.…”
mentioning
confidence: 71%
“…The Maillard reaction causes a loss of amino acids. The Maillard reaction does not require high temperatures, but the reaction rate will increase sharply with increasing temperature and drying time [30].…”
Section: Protein Contentmentioning
confidence: 99%
“…Warna merupakan salah satu faktor penentu mutu dan secara visual warna muncul pertama kali dan kadang-kadang sangat menentukan, sehingga warna menjadi ciri khas organoleptik yang penting dalam makanan (Arza & Asmira, 2017). Berdasarkan hasil uji organoleptik boba dengan penggunaan buah bit dan bubuk sari kacang merah pada F1 (buah bit 60 gr : bubuk sari kacang merah 40 gr) memiliki kriteria merah agak pucat sedangkan pada F2 (buah bit 70 gr : bubuk sari kacang merah 30 gr) dan F3 (buah bit 80 gr : bubuk sari kacang merah 20 gr) memiliki kriteria merah tua.…”
Section: Indikator Warnaunclassified
“…Warna merupakan salah satu faktor yang menentukan mutu dan secara visual warna tampil lebih dahulu dan kadangkadang sangat menentukan, sehingga warna dijadikan atribut organoleptik yang penting dalam suatu bahan pangan (Arza, 2017).…”
Section: Uji Tingkat Kesukaan (Uji Hedonik) Terhadap Kue Bingkaunclassified
“…Makanan yang memiliki rasa yang enak dan menarik akan disukai oleh konsumen (Arza, 2017). Berdasarkan Gambar 4, skor ratarata yang diperoleh dari perlakuan konsentrasi 100% tepung terigu sebesar 4,14 (sangat suka), pada konsentrasi 70% tepung terigu : 30% Tekstur merupakan sensasi tekanan yang dapat diamati dengan mulut (pada waktu digigit, dikunyah, dan ditelan) ataupun perabaan dengan jari (Yulianti, 2018).…”
Section: Gambar 3 Uji Hedonik Warna Terhadap Kue Bingkaunclassified